PELATIHAN PEMBELAJARAN SECARA DARING PADA MASA PANDEMI COVID-19 DI SDN CURUG V - Bambang Ismaya; Iif Miftahuddin; Fahrudin Fahrudin (SABA JAYA PUBLISHER, 2023)
The Covid-19 pandemic has had quite a big impact on the lives of Indonesian people, one of which is in the aspect of education. The existence of this pandemic has prompted the government to issue policies regarding the implementation of learning in Indonesia, namely learning training that must be carried out online. This study aims to analyze the online learning process during the Covid-19 pandemic at SDN Curug V class VA. This research is included in the type of phenomenological research, as for data collection techniques using observation, interviews and documentation. The results of this study illustrate that the implementation of online learning at SDN Curug V class V A has been implemented well. In implementing online learning, the teacher has carried out lesson planning and carried out learning properly using learning media, strategies, methods and learning approaches that are adapted to students. Online learning has flexibility in its implementation and is able to encourage teachers to be more creative in teaching besides that students are required to be more independent. However, online learning has obstacles including unstable network conditions and students' difficulties understanding learning material which is a challenge in itself in online learning.